A cross-sectional survey of hard ticks and molecular characterization of Rhipicephalus microplus parasitizing domestic animals of Khyber Pakhtunkhwa, Pakistan. - Muhammad Rooman (Public Library of Science (PLoS), 2021)
Background In tropical and subtropical countries, tick infestation causes major public health problems and considerable financial losses to the livestock industry. This study was aimed to assess the species composition of richness and analyze the phylogeny of Rhipicephalus microplus in the District Bannu of Khyber Pakhtunkhwa, Pakistan. Methods Collected ticks were identified morphologically and DNA extracted from R. microplus was amplified and subjected to sequencing. Results A total of 3,600 animals were examined among them 1,494 animals were found to be infested with ticks, including 669 cows, 476 buffaloes, 163 goats, and 186 sheep (p = 0.001). Tick infestation was significantly high (43.58%) in animals of age group (<1 year) (p-value = 0.027). Female animals were more (44.05%) infested with ticks than males (34.43%) (p = 0.001). The intensity of infestation was significantly higher in summer (77.49%) (p = 0.001). A total of 5,557 ticks were collected comprising three genera and six species. R. microplus was predominantly prevalent (n = 1,474; 26.52%), followed by Rhipicephalus annulatus (n = 1,215; 21.86%), Hyalomma anatolicum (n = 1,139; 20.49%), Hyalomma marginatum (n = 1,086; 19.54%), and Rhipicephalus turanicus (n = 761; 13.69%), while the least common was Haemaphysalis aciculifer (n = 80; 1.43%) (p = 0.001). Morphologically identified R. microplus species were also analyzed genetically by using two genetic markers 16S ribosomal RNA (16S rRNA) and internal transcribed spacer 2 (ITS2) genes. The phylogenetic study revealed that R. microplus is genetically diversified and clustered in clade B with R. microplus species from China, India, and Pakistan. Conclusion Ticks infestation was significantly correlated with various factors including age, sex, season, and animal type. R. microplus genetically resembled species reported from India and China. However, major knowledge gaps concerning various species of ticks exist and many areas are still unexplored in Pakistan. Therefore, it is necessary to explore the epidemiological and molecular aspects of various tick species in other regions of southern Khyber Pakhtunkhwa.